Edaphobacillus lindanitolerans gen. nov., sp. nov., isolated from hexachlorocyclohexane (HCH) contaminated soil1. (15th January 2013) - Lal, Devi; Khan, Fazlurrahman; Gupta, Sanjay Kumar; Schumann, Peter; Lal, Rup
Abstract A Gram‐staining‐positive, aerobic, cocco‐bacilli‐shaped, non‐motile, non‐spore forming, cream colored strain bacterium (strain MNA4T) was isolated from hexachlorocyclohexane (HCH) contaminated soil. Strain MNA4T showed the highest 16S rRNA gene sequence similarity of 97.47% with type species of the newly defined genus Bhargavaea cecembensis. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain MNA4T belonged to a clade represented by Bhargavaea cecembensis, Bacillus beijingensis and Bacillus ginsengi. DNA‐DNA hybridization values of the strain MNA4T with close relatives were well below the 70% threshold value recommended for delineation of species. The major fatty acids were anteiso C15:0, anteiso C17:0, iso C16:0 and iso C15:0. The strain was found to contain respiratory quinones MK‐8, MK‐9 and MK‐7 in an approximate molar ratio of 85:7:5. Polar lipid profile consisted of diphosphatidylglycerol, phosphatidylglycerol and two unknown phospholipids. The DNA G + C content was 55.6 mol%. Peptidoglycan type was A4α (L‐Lys – L‐Ala – D‐Asp). Phylogenetic analysis, fatty acids profile, phenotypic properties and chemotaxonomic data of strain MNA4T indicated that it represents a novel species of a novel genus for which the name Edaphobacillus lindanitolerans gen. nov., sp. nov., is proposed. The type strain is MNA4T (=CCM 7584T = DSM 22424T).